The Effectiveness of the Joyful Learning Approach Assisted by Instructional Media on Elementary School Students’ Mathematics Learning Outcomes: A Systematic Review (2019–2025) - Putri Septa Cahyani; Noening Andrijati; Nuni Widiarti; Arif Widiyatmoko (Papanda Publisher, 2026)
This study aims to analyze the effectiveness of the joyful learning approach combined with instructional media in improving Mathematics learning outcomes among fifth-grade elementary school students. The review was conducted using the Systematic Literature Review (SLR) method. Data sources were collected by searching documentation and reviewing all articles relevant to the keywords “joyful learning,” “instructional media,” “mathematics,” and “fifth grade.” The findings indicate that the implementation of joyful learning consistently provides a positive impact on the improvement of Mathematics learning outcomes among fifth-grade students. This approach is able to create an enjoyable, interactive, and meaningful learning atmosphere, thereby increasing students’ motivation, participation, and conceptual understanding. The use of instructional media—whether concrete, digital, or game-based—reinforces the effectiveness of joyful learning by providing varied learning experiences aligned with students’ developmental characteristics. Based on the findings, the majority of studies conclude that the combination of joyful learning and instructional media is effective for implementation in Mathematics learning to improve fifth-grade students’ learning outcomes. Thus, it can be concluded that the joyful learning approach supported by instructional media is an innovative strategy worthy of application in fifth-grade Mathematics instruction at the elementary school level